Comparative Performance Analysis of Bituminous Mixtures with EAF Steel Slags: A Laboratory Evaluation - Marco Pasetto; Nicola Baldo (The Minerals, Metals and Materials Society, 2008)
"The paper presents the results of a laboratory study, conducted at the Experimental Road Laboratory of the University of Padova, in order to verify the possibility to use different types of electric arc furnace (EAF) steel slags – in substitution of the natural aggregates – in the composition of both dense graded and porous asphalt mixes for flexible road pavements. The research has been articulated in a preliminary study of the chemical, physical, and mechanical properties of the EAF steel slags, and in the following mix design and performance characterization of the bituminous concretes, through stiffness modulus tests at various temperatures and permanent deformation (creep) tests. All the mixtures with EAF slags have satisfied the requisites for acceptance standardized for the road sector, thus resulting as suitable for use in the construction of infrastructures, moreover presenting higher mechanical characteristics than those of the corresponding asphalts with full natural aggregate. IntroductionSteel is produced industrially employing two main technologies: the integral cycle, which starts from mineral iron, and the electric cycle, which uses scrap metal. A consistent amount of the steel produced in Italy (approx. 55%) comes from Electric Arc Furnaces (EAF), which every year, alongside the steel, produce approximately 2 million tons of slag. The recycling of this waste product to produce new high-quality raw materials would reduce both the exploitation of limited natural resources and the amounts of refuse. In the European Union, 60% of slag from EAF is still today disposed of in dumps. The extremely diverse origins of scrap metal (waste from mechanical manufacturing, industrial and civil demolition, car bodywork, etc.) means that the by-products generated by the smelting, slags and ashes, contain different elements, in varying composition, also depending on the type of steel to be produced and the consequent adding of binding and melting elements during the production process. For this reason, iron and steel industry electric furnace slag - unlike the blast furnace dross utilised in cement works, which has a more uniform composition as it comes from a more standardised cycle – has been viewed in the past with some diffidence and so, at least in Italy, the possibilities of its re-use have never been fully developed."